2019
DOI: 10.1371/journal.pcbi.1006960
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the temporal dynamics of the gut microbial community in adults and infants

Abstract: Given the highly dynamic and complex nature of the human gut microbial community, the ability to identify and predict time-dependent compositional patterns of microbes is crucial to our understanding of the structure and functions of this ecosystem. One factor that could affect such time-dependent patterns is microbial interactions, wherein community composition at a given time point affects the microbial composition at a later time point. However, the field has not yet settled on the degree of this effect. Sp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 54 publications
1
48
0
Order By: Relevance
“…MTV-LMM. MTV-LMM uses a linear mixed model for identifying autoregressive taxa and predictioning their relative abundance at future time points (see Shenhav et al 48 for more details). MTV-LMM is motivated by our assumption that the temporal changes in the relative abundance of taxa j are a time-homogeneous high-order Markov process.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…MTV-LMM. MTV-LMM uses a linear mixed model for identifying autoregressive taxa and predictioning their relative abundance at future time points (see Shenhav et al 48 for more details). MTV-LMM is motivated by our assumption that the temporal changes in the relative abundance of taxa j are a time-homogeneous high-order Markov process.…”
Section: Methodsmentioning
confidence: 99%
“…We therefore sought to understand whether the initial microbiome starting point (mode of delivery) would have an impact on the identity of specific microbiome members. We applied our newly developed tool utilizing a linear mixed modelbased method to predict microbial community temporal dynamics 48 (see Methods: MTV-LMM). Using this method, we quantified the dependence and predictability of the relative abundance of each microbe in our dataset at a given time point, based on the microbial community composition at previous time points (1, .., t − 1).…”
Section: Mode Of Delivery In Birth Drives Historical Contingency Effementioning
confidence: 99%
“…Li et al [34] suggest addressing this by inference of the latent overall biomass. Alternatively, Shenhav et al [21] suggested a linear mixed model with variance components, while representing the previous state microbial community using its quantiles instead of relative abundances. Yet, binning taxa into quantiles may lose fine-grained information about interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Mathematical models can describe and predict ecosystems. A previous study suggested that the composition of the human faecal microbiome at a given time point is a major factor defining microbiome composition 11 . We hypothesized that mathematical modelling can streamline the clinical management of the gut microbiota.…”
Section: Introductionmentioning
confidence: 99%